The role of employee well-being and work resilience in supporting career satisfaction / Puji Asmanto and Olivia Fachrunnisa - Asmanto, Puji; Fachrunnisa, Olivia (Universiti Teknologi MARA, Terengganu, 2024)
This research aims to examine career experience and employee well-being influence work resilience, to increase career satisfaction in a company in the electricity sector in Indonesia. This organisation has its own business process that involves many entities through a Finance Lease Agreement. Through the use of quantitative analysis with stratified random sampling techniques, a total of 93 participants were obtained which were considered to represent a sample of the entire organization. The empirical model was evaluated using the Smart PLS Program to verify the significance of the external model and its internal model. Research findings show that employee well-being has a direct impact on job resilience which in turn increasing career satisfaction. However, we found that career experience did not influence work resilience. This research used Conservation of Resource Theory (Hobfoll, 1989) and Career Development Theory (Supers, 1957) as theoretical framework. The combination of these two theories explains that managed and adapted resources, according to The COR theory, can become the basis for individual career growth and adaptation, in line with the Supers career development principle. These findings indicate a lack of support for the expected relationship between career experience and job resilience, as suggested by Khan's (2017) previous research and its two hypotheses. This gap challenges previous research that found a positive and significant influence of career experience on job resilience. Organizations must assess how initiatives or tactics increase employee resilience to increase career satisfaction.